2021
DOI: 10.1021/acs.orglett.1c03035
|View full text |Cite
|
Sign up to set email alerts
|

Access to Polycyclic Thienoindolines via Formal [2+2+1] Cyclization of Alkynyl Indoles with S8 and K2S

Abstract: The syntheses of polycyclic thienoindolines bearing a dihydrothiophene or tetrahydrothiophene subunit have not been reported, despite the fact that such compounds may have interesting medicinal properties. Herein, we report a protocol for accessing polycyclic dihydrothiophenes by means of formal [2+2+1] intramolecular dearomatizing cyclization of alkynyl indoles with K2S and S8 as the sources of sulfide. In addition, tetrahydrothienoindolines were stereoselectively synthesized via a one-pot, two-step protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…33 α-Ketothioester 42a was obtained on gram scale in 74% yield and it was shown that the reaction can be applied to various combinations of α-hydroxy ketones and alkyl halides. The 1,2-dicarbonyl reagents were then used to prepare natural products and dicarbonyl-containing drugs such as indibulin (43) and polyandrocarpamide C (44), as well as 9,10-phenanthrenequinone (45) (Scheme 13).…”
Section: C-h Bond Thiolationmentioning
confidence: 99%
See 2 more Smart Citations
“…33 α-Ketothioester 42a was obtained on gram scale in 74% yield and it was shown that the reaction can be applied to various combinations of α-hydroxy ketones and alkyl halides. The 1,2-dicarbonyl reagents were then used to prepare natural products and dicarbonyl-containing drugs such as indibulin (43) and polyandrocarpamide C (44), as well as 9,10-phenanthrenequinone (45) (Scheme 13).…”
Section: C-h Bond Thiolationmentioning
confidence: 99%
“…Tetrahydrothienoindolines 114 were also stereoselectively constructed via a AgNO 3 -catalyzed alkenyl dearomatization followed by two nucleophilic addition reactions involving K 2 S (Scheme 37). 43 A key intermediate of this formal [2 + 2 + 1] intramolecular dearomatizing cyclization is the formation of S 3…”
Section: [2 + 2 + 1] Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic & Biomolecular Chemistry fide anions. [32][33][34][35][36][37][38] The in situ generated active species may be used under metal-free conditions to create new C-S bonds by the atom efficient sulfuration of electrophiles, e.g. CvN double bonds, 39,40 isocyanides, 29,37,[41][42][43] isothiocyanates 44 and iodonium salts.…”
Section: Papermentioning
confidence: 99%
“…Certain nucleophiles, such as aliphatic amines, sulfide anions, carbonates and hydroxides are able to activate sulfur under mild conditions, generating open-chain ionic polysulfide anions. 32–38 The in situ generated active species may be used under metal-free conditions to create new C–S bonds by the atom efficient sulfuration of electrophiles, e.g. CN double bonds, 39,40 isocyanides, 29,37,41–43 isothiocyanates 44 and iodonium salts.…”
Section: Introductionmentioning
confidence: 99%